Immunomodulatory Molecular Mechanisms of Luffa cylindrica for Downy Mildews Resistance Induced by Growth-Promoting Endophytic Fungi - Mamoona Rauf; Asim Ur-Rahman; Muhammad Arif; Humaira Gul; Aziz Ud-Din; Muhammad Hamayun; In-Jung Lee (Journal of Fungi, 2022)
Downy mildew (DM), caused by P. cubensis, is harmful to cucurbits including luffa, with increased shortcomings associated with its control through cultural practices, chemical fungicides, and resistant cultivars; there is a prompt need for an effective, eco-friendly, economical, and safe biocontrol approach. Current research is therefore dealt with the biocontrol of luffa DM1 through the endophytic fungi (EF) consortium. Results revealed that T. harzianum (ThM9) and T. virens (TvA1) showed pathogen-dependent inducible metabolic production of squalene and gliotoxins by higher gene expression induction of SQS1/ERG9 (squalene synthase) and GliP (non-ribosomal peptide synthetase). Gene expression of lytic enzymes of EF was also induced with subsequently higher enzyme activities upon confrontation with P. cubensis. EF-inoculated luffa seeds showed efficient germination with enhanced growth potential and vigor of seedlings. EF-inoculated plants showed an increased level of growth-promoting hormone GA with higher gene expression of GA2OX8. EF-pre-inoculated seedlings were resistant to DM and showed an increased GSH content and antioxidant enzyme activities (SOD, CAT, POD). The level of MDA, H2O2, REL, and disease severity was reduced by EF. ACC, JA, ABA, and SA were overproduced along with higher gene expression of LOX, ERF, NCED2, and PAL. Expression of defense-marker genes (PPO, CAT2, SOD, APX, PER5, LOX, NBS-LRR, PSY, CAS, Ubi, MLP43) was also modulated in EF-inoculated infected plants. Current research supported the use of EF inoculation to effectively escalate the systemic immunity against DM corresponding to the significant promotion of induced systemic resistance (ISR) and systemic acquired resistance (SAR) responses through initiating the defense mechanism by SA, ABA, ET, and JA biosynthesis and signaling pathways in luffa.